Natural Stone Cluster and Valorpedra Association in Portugal: Collective efficiency, promotion and marketing strategies in the appreciation of the Dimension Stones production chain in Portugal - Lopes, Luís (2014)
The Natural Stone Cluster recognition by the Portuguese government resulted in the establishment of Valorpedra Association (VAPE). This national recognition allow development and increase competitiveness of the Dimension Stone Sector for which specific funds were available. The implemented measures potentiated networking among enterprises and development of partnership projects. VAPE is a nonprofit association that manages and promotes Natural Stone Cluster, seeking a Strategy for Collective Efficiency. Its mission is to implement initiatives relating to Mineral Resources for innovation, qualification and modernization of the industry. It also aims to strengthen cooperation among companies, business associations, technology centers, R & D, training centres and other entities, thus contributing to the implementation of technology transfer processes, and therefor increase productivity, competitiveness and innovation. As a strategy to achieve the mission objectives is proposed to consolidate and invest in the conquest of foreigners markets, strong and precise resources classification and technological, productive innovation and territorial organization. Since Cluster the activities beginning on 17 July 2009 to March 2014, € 57,831,802.00 were invested, corresponding to € 38,246,879.00 of government support and € 19,584,923.00 to equity investors. Thus, in countercyclical with a general downturn of the Portuguese economy, in 2013 the Natural Stone sector grew 28%. These results were made possible thanks to marketing and promotion strategies undertaken in major international fairs and underpinned by recognition of the Natural Stone Cluster as the relevant economic activity sector for the country. This work presents the principal measures that have been implemented, the projects developed and the most important results achieved in each of them. References CEVALOR (2006) – Estudo Estratégico Prospectivo 2004 – 2006, 88. CEVALOR (2008) – Candidatura: Estratégias de Eficiência Colectiva – Cluster da Pedra Natural, 88. CEVALOR (2009) – Cluster da Pedra Natural, Reformulação do Programa de Acção. Candidatura às Estratégias de Eficiência Colectiva (EEC) - Reconhecimento do Cluster da Pedra Natural, 112. Luís Lopes, Nelson Cristo, Marta Peres, Nuno Bonito, Ruben Martins, António Dieb & Jorge Carvalho Edgar B. A. e Maria J. D.C. Ed., Técnicas Aplicadas a la Caracterización y Aprovechamiento de Recursos Geológico-Mineros, Volumen III: Interacción com la Sociedad, 178 p., Red Mineria XXI, CYTED e Instituto Geológico y Minero de Espanha. ISBN 978-84-15413-13-4. http://hdl.handle.net/10174/7836.